Counseling Regarding Stunting Prevention in Toddlers - Irmayani, Irmayani; Ginting, Rosita; Samura, Jul Asdar; Parinduri, Anggi (JURNAL PENGMAS KESTRA (JPK), 2024)
Stunting is a serious challenge because it can hinder a child's growth and development. This condition is triggered by malnutrition, repeated infections, and lack of adequate psychosocial stimulation, and is characterized by the child's height being below the appropriate standard. The main causes of stunting are poor parenting patterns, unhealthy eating patterns for pregnant and breastfeeding mothers, lack of nutritional and protein intake, and children's high vulnerability to disease. This community service activity was carried out in Sidoharjo Village – I Pasar Miring, Pagar Merbau District, Deli Serdang Regency with a total of 26 participants. The aim of this activity is to provide education regarding stunting prevention in Sidoharjo Village – I Pasar Miring. The main target of this counseling is mothers who have children under five. Implementation of this activity involves collaboration with village officials and village midwives. The method used was presentation of material through lectures and giving leaflets. The material presented includes the concept of stunting, its causes, symptoms, and how to prevent it, including information regarding the contents of my plate. The results of this activity show an increase in participants' understanding of stunting, its causes, symptoms and how to prevent it. In addition, there is increased awareness in dealing with the symptoms of stunting, with the hope of reducing the risk of stunting in children. It is hoped that in the future, activities like this will continue to be carried out so that stunting in toddlers can be avoided.